Enhancing harvested rainwater quality through nanofiltration and storage practices in a rural community - Raveen Rathilall; Blessing George Akpan (Interdisciplinary Journal of Rural and Community Studies, 2025)
Water scarcity remains a persistent global challenge, particularly in rural communities where untreated harvested rainwater is often the primary source of water for domestic use. This study investigated cost-effective strategies to improve the quality of harvested rainwater in a selected rural community in South Africa. A sequential mixed-methods approach was adopted to explore the community’s existing rainwater harvesting practices, associated challenges, and perceptions of rainwater harvesting. The quantitative part of the study gathered data from 221 households through convenience sampling and was analysed using inferential statistics. The qualitative part of the study gathered insights from 16 interviews using convenience-based voluntary sampling and was analysed thematically. The results revealed that the majority of the households collected and stored rainwater using rooftop harvesting systems combined with plastic storage tanks. The harvested rainwater was primarily used for cooking, drinking, and cleaning. However, contamination from inadequate storage conditions, lack of filtration systems, and exposure to environmental pollutants frequently resulted in health-related concerns surfacing within the community. The study proposes using a simple wood-based nanofiltration system as a low-cost sustainable intervention to improve water quality. In addition, the study recommends promoting hygienic practices to reduce contamination risks and improving storage practices to preserve water quality. By advocating for accessible filtration technologies and encouraging safer water storage practices, the study contributes to the advancement of safe rainwater harvesting and sustainable water management in rural communities.